Sustainability learning based on the Andean Amazonian Cosmo vision - Salinas Gamero, Teresa (2019)
This research has three aspects in relation to Education Innovation for the Sustainable Development: (i) changes in the philosophical, epistemological and didactic framework of education, (ii) the questioning of the new functions of the higher education and (iii) the evaluation and inclusion of an Andean Amazonian Cosmo vision and rationality in the University environment. One of the transformer results of this experience was to put into practice complex, transdisciplinary, phenomenological and hermeneutical education researches that promote an intercultural dialogue. It was developed in the «Diplomado en Biodiversidad y Saberes interculturales» (Diploma course in Biodiversity and Intercultural Knowledge) that took place in the San Martin region in the Quechua Lamas communities. It was organized by the Instituto Peruano del Pensamiento Complejo Edgar Morin -IPCEM (Peruvian Institute for Complex Thought Edgar Morin –IPCEM) with the German cooperation funding of the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH and the United Natiosn Environment Programme. It was also support by the academic regional council constituted by local organizations and the «WamanWasi» centre. The UNU Institute for the Advanced Study of Sustainability (UNU-IAS) recognized thisexperience with the RCE Award for Outstanding Flagship Project in the 9th Global RCE Conferencerealized in 2014 in Okayama, Japan.